Romantic Love: Mechanism for Feminist Empowerment or Orientalist Legacy? - Lee, Min Joo (SARE: Southeast Asian Review of English, 2019)
In this article, I analyze the romantic desire of non-Korean – particularly Western – women for the fictional Korean male characters depicted in transnationally popular Korean television dramas. This article is divided into two sections: first, it examines the transnational popularity of the South Korean television drama series, My Love from Another Star, and its depiction of a particular type of romantic Korean masculinity called kkonminam (flower boy) masculinity. Here, I argue that these fictional stories problematize hypersexual masculinity through their representations of romantic masculinity. The second section of the article extends the analysis by deploying ethnographic interviews and participant-observations of Western fans of Korean television dramas who, believing that the kkonminam depicted in the dramas are true reflections of Korean men, travel to Korea to form romantic relations with Korean men in real life. Using feminist theories of love, such as those propounded by bell hooks and Lauren Berlant, and the theory of the erotic by Audre Lorde, I argue that these fans, while romantically desiring Korean kkonminam, also co-opt the discourse of romantic love and Korean romantic masculinity to articulate and essentialize cultural differences between the East and West.